(untitled) (Research, Society and Development, 2022)
The objective of this study was to identify the global scientific production regarding transsexuals, transvestites, and transgender people, concerning the volume of publications, their temporal dynamics, and the countries of publication. This is a bibliometric review with data collection carried out between April and July 2022, by consulting the bibliographic databases Latin American and Caribbean Literature in Health Sciences, MEDLINE via PubMed, and the Virtual Health Library. A total of 923 publications were included, of which 57.10% were published in journals in the United States of America, 20.91% in England, and 7.48% in Brazil. There was an increase in the frequency of publications worldwide in the period from 2010 to 2016, with an annual percentage change of 58.2% (95% CI: 40.8 - 77.8), and, in the final period of the historical series from 2016 to 2021 of 19.9% per year (95% CI: 2.8 - 39.9). Publications have become more heterogeneous among the various areas of scientific knowledge, and, although the large areas of health have greater relevance in the number of publications, a greater diversity of studies in the academic environment stands out. Thus, new public policies can be formulated and applied to deepen health actions in Brazil and the world, as well as new strategies for social debate and expansion of themes in scientific research.